Analysis of an intergenerational service-learning experience based on physical exercise in a community setting: a mixed-method study - Beatriz Alonso-Cortés Fradejas; Raquel Lafuente-Ureta; Sandra Calvo; Sandra Calvo; Mario Fernández-Gorgojo; Jose Lesmes Poveda-López; Carolina Jiménez-Sánchez; Carolina Jiménez-Sánchez (Frontiers in Public Health)
IntroductionPhysical activity offers numerous benefits that improve psychological well-being, reduce dependency, and foster intergenerational relationships. Universities play a key role in promoting the health of students by proposing actions that contribute to a sustainable future, fostering a mature society and reducing ageism. This service-learning project aimed to assess the impact of an intergenerational cane-walking program on older adults and physiotherapy students in a community setting. The project focused on promoting health and fostering intergenerational relationships.MethodsA concurrent, nested mixed-methods design was used for the intervention, involving intergenerational group walks during the 2022–2023 academic year. The program was designed and supervised by faculty members and three fourth-year fellows. Data collection was based on adherence to the intervention, the Behavioral Regulation in Exercise Questionnaire (BREQ-3), interviews with older adults and feedback questionnaires completed by them and participating students.ResultsSatisfactory adherence was evidenced among older adults, with 65.79% of participants who completed the project and 72% who adhered to the intervention, although there were no statistically significant differences in terms of motivation to exercise taking that adherence into account. The project’s ability to foster intergenerational relationships was rated by the seniors at 9.50 ± 0.6, and 100% answered affirmatively about its capacity of contribute to improving their health and well-being. Student feedback also reflected high scores for fostering intergenerational relationships, with scores of 10 (fellows), 8.7 ± 1.2 (third-year students), and 8.27 ± 1.2 (second-year students). The project’s contribution to skills development was rated positively by 100% of the fellows, 88.6% of the second-year students, and 74.1% of the third-year students. In the nested study, three key themes related to exercise emerged by older adults: (1) perceptions of exercise, (2) barriers to exercise and (3) motivations for exercise. Regarding satisfaction with the program, three main themes emerged: (1) intergenerational relationships, (2) strengths of the program and (3) suggestions for improvement.ConclusionThe program appears to improve the well-being of older adults and provide valuable experiential learning for students. Thus, service-learning projects could effectively promote sustainable health practices, highlighting the important role of universities in community health initiatives.